Clinical Assessment of Peripheral Arterial Disease in the Office: What Do the Guidelines Say? - Tummala, Srini; Scherbel, Derek (Seminars in Interventional Radiology, 2018)
Lower extremity peripheral arterial disease (PAD) is the manifestation of atherosclerotic disease within the lower extremities. The presentation of PAD is diverse ranging from asymptomatic disease to claudication or to debilitating rest pain, nonhealing ulcers, and gangrene. PAD is associated with significant morbidity, mortality, and healthcare costs. Proper diagnosis and management of PAD is important so as to maintain quality of life and reduce the risk of cardiovascular disease and adverse limb events such as amputation. This document provides a comprehensive outpatient approach to the clinical assessment of PAD that includes risk factors, diagnosis, treatment, and follow-up options.
Keywords: peripheral artery disease; guidelines; outpatient; critical limb ischemia; claudication; interventional radiology